2018
DOI: 10.1016/j.molmet.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal bitter taste receptor activation alters hormone secretion and imparts metabolic benefits

Abstract: ObjectivesExtracts of the hops plant have been shown to reduce weight and insulin resistance in rodents and humans, but elucidation of the mechanisms responsible for these benefits has been hindered by the use of heterogeneous hops-derived mixtures. Because hop extracts are used as flavoring agents for their bitter properties, we hypothesized that bitter taste receptors (Tas2rs) could be mediating their beneficial effects in metabolic disease. Studies have shown that exposure of cultured enteroendocrine cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 75 publications
(113 reference statements)
3
97
0
Order By: Relevance
“…Additionally, the broadly tuned (30) bitter agonist chloroquine (TAS2R3, ‐R7, ‐RIO, ‐R14, and ‐R39; P < 0.05) and the more selective bitter agonists (30, 31) emetine (TAS2R1, indirect evidence; P < 0.001) and 1,10‐phenanthroline (TAS2R5; P < 0.05) also increased ghrelin secretion in a concentration‐dependent manner in fundic cultures from obese patients (Fig. 3 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the broadly tuned (30) bitter agonist chloroquine (TAS2R3, ‐R7, ‐RIO, ‐R14, and ‐R39; P < 0.05) and the more selective bitter agonists (30, 31) emetine (TAS2R1, indirect evidence; P < 0.001) and 1,10‐phenanthroline (TAS2R5; P < 0.05) also increased ghrelin secretion in a concentration‐dependent manner in fundic cultures from obese patients (Fig. 3 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Kok et al . (31) showed that KTD‐501, a pure derivative of a hops iso‐humulone present in beer, stimulated GLP‐1 secretion and improved several features of the metabolic syndrome in diet‐induced obese mice. The effect was mimicked by emetine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…93 Indeed, a nonfunctional haplotype of human TAS2R9 has been associated with an increased risk for type II diabetes. 89 Recently, it was demonstrated that a synthetic bitter substance activating mouse Tas2r108, a receptor expressed in the small intestine and STC-1 cells, is capable of inducing GLP-1 secretion and improving the metabolic state in a mouse model, 94 thus confirming a role of bitter signalling in digestive processes.…”
Section: Intestinementioning
confidence: 93%
“…66 In rodents, stimulation of intestinal bitter taste receptors induces GLP-1 secretion and weight loss and improves glucose tolerance. 67,68 There is limited information about bitter taste receptor activation in humans, with some evidence that it may alter gastrointestinal motility and hunger. 69 Hitherto, no study has evaluated effects on GLP-1 secretion or glycaemic control.…”
Section: Bile Acids and Glp-1mentioning
confidence: 99%